Tanakpur Barrage Thirteen Year Saga of the Nepal Canal Sill Level - Pun, Santa Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
The Tanakpur Barrage was constructed by India in the 1980s on her territory on the Mahakali river, as an "alternative" to the aging 1920 Sarada barrage, to irrigate 1.61 million hectares of land in India. The sill level of the Tanakpur regulator for the Nepal canal is EL 245 meters, which is 3.5 meters (11.5 feet) higher than the sill level for the corresponding regulator for India. India stresses that specified quantity of water flow for Nepal will be assured as the pond level of the barrage for power generation will be maintained at EL 246.7 meters. Such promises were made on the Gandak barrage, which also has a powerhouse on the canal, but as the pond level was not maintained, Nepal never got the specified quantity of water from the Gandak barrage. Over the last 13 years, India has been totally deaf to Nepal's request to lower the sill level. Instead, India, argues that the Tanakpur regulator for Nepal was already "constructed in 1992 before the treaty." India's modus operandi, whether for the Farakka, Tanakpur, or Laxmanpur barrages or the Mahali Sagar, Rasiawal-Khurd-Lotan, Kalkalwa-Holiya bunds, has always been to construct first then, over the years, formalize it. Like many of the structures along the Indo-Nepal border, if Nepal does not take a firm stand then the Nepal canal sill level at Tanakpur is heading to be another fait accompli, for Nepal. Key words: Tanakpur barrage; Sill level; Sarada barrage; Mahakali Treaty; India; Nepal DOI: 10.3126/hn.v5i0.2476 Hydro Nepal Vol. 5, July 2009 Page:2-7